Maximum Likelihood Based Approach for Weibull’s Distribution Parameters Estimation for Wind Energy Applications - Akim Salami, Adekunlé; Mawugno Kodjo, Koffi; Sénah Akoda Ajavon, Ayité; Agbeblewu Dotche, Koffi; Bédja, Koffi-Sa (International Journal of Engineering and Technology, 2019)
In this article, a new computational approach is proposed to estimate the Weibullâ€™s distribution parameters. The method is dependent on the Maximum Likelihood (MLM) using the even and odd classes of wind speedâ€™s distribution. This new approach is referred to either as Maximum Likelihood with Odd Bins time series Method (MLOBM) or Maximum Likelihood with Even Bins time series Method (MLEBM). It comprises the data size reduction, which in turns may lead to a fast processing time. This method was evaluated in a comparative analysis of MLOBM and MLEBM against the proposed theoretical model. The obtained results on the mean wind speed, standard deviation, and power density on monthly and annual scales for different geographical locations may indicate that the MLOBM or MLEBM may give a better estimate of the Weibull parameters with a low error. Â Â